Translation Techniques and Translation Competence in Translating Informative Text for Indonesian EFL Learners - Hanna Sundari; Rina Husnaini Febriyanti (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2017)
foreign learner on studying English. This study aims at analyzing and describing translation techniques and translation competence of Indonesian EFL learners. The research was carried by descriptive research method. The number of respondent is 35 students on majoring of English Education, and the translation test as the instrument. The result of descriptive analysis shows that the literal translation technique (word by word) is mostly used. Moreover, the other techniques, sorting from the highest percentage, are free translation technique, omission, addition, and compensation, replacement of word class, explication-implication, and paraphrase. Moreover, the translation competence of respondents was on 48.57% in the interval scores 60-70. With the average score of 72, 34, the translation competence achieved by the respondents is categorized as fair. Therefore, translation competence by the source text is quite fair organized with comprehending of the content sufficiently, yet there is still mistake on diction, grammar, punctuation and word selection influencing the quality of the translated target text.